Migration, Spillovers, and Trade Diversion : The Impact of Internationalization on Stock Market Liquidity - Levine, Ross; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
What is the impact of firms that cross-list, issue depositary receipts, or raise capital in international stock markets on the liquidity of remaining firms in domestic markets? Using a panel of over 3,200 firms from 55 countries during 1989-2000, Levine and Schmukler find that internationalization reduces the liquidity of domestic firms through two channels. First, the trading of international firms migrates from domestic to international markets and the reduction in domestic liquidity of international firms has negative spillover effects on domestic firm liquidity. Second, there is trade diversion within domestic markets as liquidity shifts out of domestic firms and into international firms.